1949
DOI: 10.1146/annurev.mi.03.100149.001111
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Basis of Immunity

Abstract: Once invading organisms or other antigenic materials have passed or have been introduced beyond the epithelial or mechani cal barriers, their localization and disposal is a part of local (local inflammation) and general defense reactions. The main functional roles of the cells involved in these reactions are (a) to remove foreign material by extra-or intracellular digestion (phagocytosis) or to isolate it by a connective tissue wall (encapsulation); (b) to perform various reparative processes; and (c) to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
1

Year Published

1951
1951
1978
1978

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 52 publications
1
16
1
1
Order By: Relevance
“…The literature contains many conflicting discussions about the interrelationships of antibody formation, the reticulo-endothelial system, lymphoid tissue, and the adrenal cortex (13,14). With immunization, several morphological changes are known to occur, most of which were observed in this study.…”
Section: Discussionmentioning
confidence: 61%
“…The literature contains many conflicting discussions about the interrelationships of antibody formation, the reticulo-endothelial system, lymphoid tissue, and the adrenal cortex (13,14). With immunization, several morphological changes are known to occur, most of which were observed in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Dixon, Weigle, and Roberts (1957), for example, have shown that transfer of suspensions of lymph node cells from immune animals to irradiated recipients can give rise in the latter to secondary responses of serum antibody. The relationship between macrophages, lymphocytes, and plasma cells developmentally and histologically is still a matter for dispute; but at present it seems justifiable to adopt the view of Burnet (1959), based on the suggestions of Taliaferro (1949), that mesenchymal cells with the inherent power of globulin production may, under appropriate conditions, take the form of stem cell, macrophage, lymphocyte, or plasma cell.…”
Section: Annals Of the Rheumatic Diseasesmentioning
confidence: 99%
“…These conclusions are based on careful histological ob servations and have been partially supported by Farr (43) using diamino acridine dye tracers. Others [44; and reviews by Rebuck (45); Taliaferro (46); and Yoffey (47) ] have described the importance of these cell trans formations in immunity. Against this view of the activities of the lympho cyte may be the failure of lymphocyte transfusions in the irradiated rat (48) or of spleen-shielding during irradiation of the rabbit (49) to increase sur vival rate or hasten recovery of the granulocytes.…”
Section: Lymphocytesmentioning
confidence: 99%